Peran Festival Erau sebagai Penguatan Identitas Sosial Melalui Kearifan Lokal - Hubaib, Futum (representamen, 2021)
This study aims to determine the role of the Erau Festival through local wisdom in an effort to strengthen social identity in the new adaptation era. Kutai Kartanegara Regency has a variety of cultures that live side by side, in harmony and peace. There are many ethnic groups who live in Kutai Kartanegara Regency and still carry their culture of origin, including Sumatra, Java, Sulawesi, Kalimantan to Nusa Tenggara. The number of immigrants is increasing over time, it is estimated that someday the number of immigrants will exceed the original population. Although the number of immigrants in Kutai Kartanegara Regency is quite large, their presence does not change the role of local culture that has been deeply rooted in the people of Kutai Kartanegara Regency. This study uses a qualitative approach with descriptive methods. Data obtained through observation, interviews, and documentation. The results showed that: (1) the relevance of local wisdom to strengthening social identity because the value of local wisdom is not an obstacle in the era of globalization, but is a major force in building regional social identity; (2). The erau festival reflects local wisdom. Keywords: Erau, Kutai Kartanegara, Local Wisdom